Blockchain privacy and regulatory compliance: Towards a practical equilibrium - Vitalik Buterin; Jacob Illum; Matthias Nadler; Fabian Schär; Ameen Soleimani (Blockchain: Research and Applications, 2024)
We study Privacy Pools, a novel smart contract-based privacy-enhancing protocol. The protocol introduces a mechanism for users to reveal certain properties of their transaction without having to reveal the transaction itself. The core concept involves allowing users to publish a zero-knowledge proof, demonstrating that their funds (do not) originate from known (un-)lawful sources, without publicly revealing their entire transaction history. This is achieved by proving membership in custom association sets, which are designed to demonstrate compliance with regulatory frameworks or social consensus. We illustrate how this mechanism can create a separating equilibrium between compliant and non-compliant withdrawals. Our work describes the technical underpinnings, incentives, and broader implications of this mechanism, highlighting how Privacy Pools-like protocols can create more private yet compliant blockchain transactions.